1964
DOI: 10.1002/ar.1091500416
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomical and neurohistological observations on the tongues of pigmy and common marmosets

Abstract: Macroscopic and neurohistological observation 3 of the tongues of the pigmy and common marmosets are described. On the dorsum, there are three circumvallate papillae arranged i n an inverted V-shape. Through the magnifying glass the foliate papillae with a few clefts are found anterior to i:he attachment of the glossopalatine fold. The fungiform papillae can be seen with a lens. The vallate papillae are supplied with abundant nerves. The taste buds are located only in the lateral non-cornified wall of the papi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0
1

Year Published

1966
1966
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 10 publications
6
19
0
1
Order By: Relevance
“…The histological observations after the silver impregnation method exhibited the thick epithelial layer with keratinized epithelial cells. The data revealed that the characteristic of sensory nerve fibers found in the connective tissue of fungiform and vallate papilla are similar to those reported by Nakayama (1943), Gairns (1956) and Nakai (1960) in the human tongue mucosa, by Okano (1953) in the dog´s tongue, Kamada (1955) in oral mucosa of ca, Kubota (1964) in the tongue of pimy and commom marmosets, Kubota et al (1966) in the tongue of squirrel monkeys, and by Kubota & Iwamoto (1967) in the tongue of slow loris. The nerve fiber bundles found the sub-epithelial connective tissue of these papillae in the tongue mucosae are different from those reported by Dixon (1961), Gairns & Aitchison (1950), Gairns (1951Gairns ( , 1956, and Rapp et al (1957) in gingival mucosa.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The histological observations after the silver impregnation method exhibited the thick epithelial layer with keratinized epithelial cells. The data revealed that the characteristic of sensory nerve fibers found in the connective tissue of fungiform and vallate papilla are similar to those reported by Nakayama (1943), Gairns (1956) and Nakai (1960) in the human tongue mucosa, by Okano (1953) in the dog´s tongue, Kamada (1955) in oral mucosa of ca, Kubota (1964) in the tongue of pimy and commom marmosets, Kubota et al (1966) in the tongue of squirrel monkeys, and by Kubota & Iwamoto (1967) in the tongue of slow loris. The nerve fiber bundles found the sub-epithelial connective tissue of these papillae in the tongue mucosae are different from those reported by Dixon (1961), Gairns & Aitchison (1950), Gairns (1951Gairns ( , 1956, and Rapp et al (1957) in gingival mucosa.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, different types of nerve endings in the oral mucosa of mammals such as lip mucosa of cat were reported by Civarelli (1908); in the pharyngeal mucosa of cats by Kamada (1955) and Eto (1959). Kubota (1964) and Kubota et al (1966) found sensory nerve fibers in the mouth mucosa of rhesus. The aim of this paper is to elucidate the presence of several types of sensory innervation of the dorsal surface of the tongue mucosa of White-lipped peccary especially in the filliform, fungiform and vallate papillae using the silver impregnation method.…”
Section: Introductionmentioning
confidence: 96%
“…Kubota & Hayama (1964) and Kubota & Togawa noted that in the lateral wall of the vallate papilla of the wild rats, the taste buds present abundant innervation similar to those observed in our data. Also, it was demonstrated that in the aging rats the nerve fibers may present the variation in the diameter and the thickness of myelin sheets.…”
Section: Discussionsupporting
confidence: 90%
“…Three vallate papillae were also found on the tongues of marsupials (Kubota et al, 1963;Krause and Cutts, 1982;Kobayashi et al, 2003;Emura, 2011), primates (Kubota and Hayama, 1964;Emura et al, 2002a), rodents (Kubota and Togawa, 1966;Emura et al, 1999), lagomorphs (Kubota, 1966), insectivores (Chunhabundit et al, 1992) and Chiroptera (Emura et al, 2001;Emura et al, 2002b). In this study, the brush-tailed rat kangaroo showed a triangular arrangement of the three vallate papillae, with the apex of the triangle directed posteriorly.…”
Section: Discussionsupporting
confidence: 55%